Ordered structures and sub-5 nm line patterns from rod–coil hybrids containing oligo(dimethylsiloxane). Issue 71 (6th August 2020) - Yang, Weilu; Zhang, Wei; Luo, Longfei; Lyu, Xiaolin; Xiao, Anqi; Shen, Zhihao; Fan, Xing-He
Abstract : Oligo(dimethylsiloxane)-based rod–coil liquid crystals can form lamellar, double gyroid, and columnar phases that can also be transferred onto a silicone substrate and oriented by modified trenches. Abstract : Sub-5 nm ordered nanostructures including lamellar, double gyroid, and columnar phases are formed by a series of oligo(dimethylsiloxane) (ODMS)-based rod–coil liquid crystals with accurate molecular weights. Films with well-oriented line patterns can be obtained by substrate-induced directed self-assembly, which may be further used as lithographic templates.